Preparation method of composite photocatalytic material for degrading sulfamethoxazole
By loading and assembling specific organic matter and nanocrystals on the surface of the foam copper matrix, composite photocatalytic materials with wide absorption spectrum, high photocatalytic activity and high stability were prepared, and the problem of low photocatalytic efficiency of existing photocatalytic materials was solved and achieved Highly effective degradation of sulfamethoxazole.
Patent Information
- Application Number
- CN202411551384.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The absorption spectrum of existing photocatalytic degradation materials is narrow, and they can only use ultraviolet light for photocatalytic degradation, resulting in low photocatalytic efficiency and the goal of scale and efficient industrial treatment cannot be achieved.
By loading linear poly[(2,5-dibromobromo-4-carbonylthiophene)-(2,5-diamidethiophene)] on the surface of the foamed copper matrix and converting to crosslinked poly[(2,5-dimethylamidethiophene)] Aminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidethiophene)], and then Bi2GdO3SeI nanocrystals are assembled on its surface to prepare composite light with wide absorption spectrum, high photocatalytic activity and high stability Catalytic materials.
The high-efficiency photocatalytic degradation of sulfamethoxazole by composite photocatalytic materials under visible and ultraviolet light conditions is achieved, and the material is highly stable and suitable for industrial applications.
Smart Images

Figure CN119406458A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photocatalytic degradation materials for sewage treatment, in particular to a method for preparing a composite photocatalytic material for degrading sulfamethoxazole. Background Art
[0002] With the development of economy and medical industry, my country has become the world's largest producer and user of sulfonamide antibiotics. However, the production process of sulfonamide antibiotics produces a large amount of wastewater containing sulfonamide antibiotics. At the same time, these antibiotics will enter the water body with their excrement after being consumed by humans and livestock, which will further lead to the formation of wastewater containing sulfonamide antibiotics.
[0003] In recent years, the detection rate and concentration of sulfamethoxazole in environmental water bodies have ranked first among sulfonamide antibiotics. Sulfamethoxazole is relatively stable in water bodies, difficult to degrade, and easy to migrate. It has direct biological toxicity and can lead to bacterial resistance and the spread of resistance genes, posing a serious threat to human health and the ecological environment. Therefore, the effective treatment of wastewater containing sulfamethoxazole has become a key issue that needs to be urgently addressed for the sustainable development of my country's economy.
[0004] The method of photocatalytic degradation of antibiotics is based on the fact that under light conditions, photogenerated electrons in photocatalytic materials transition to generate photogenerated electron-hole pairs, which react with antibiotics adsorbed on the photocatalytic materials to degrade the antibiotics. Therefore, photocatalytic degradation of antibiotics is a potential method for effectively treating wastewater containing sulfamethoxazole. However, the absorption spectrum of the photocatalytic degradation materials currently used is relatively narrow, and photocatalytic degradation can only be performed using ultraviolet light, resulting in low photocatalytic efficiency and the inability to achieve large-scale and efficient industrial treatment goals. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a composite photocatalytic material for degrading sulfamethoxazole. The photocatalytic degradation material prepared by the method has photocatalytic degradation properties such as a wide absorption spectrum, high photocatalytic activity and high stability.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] The present invention provides a method for preparing a composite photocatalytic material for degrading sulfamethoxazole, comprising the following steps:
[0008] Step [1] Loading linear poly [(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of a foam copper substrate;
[0009] Step [2] converting the linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] into a cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)];
[0010] Step [3] assembles Bi2GdO3SeI nanocrystals on the surface of the cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)]
[0011] Preferably, the step [1] specifically includes the following operations:
[0012] a1. Add 2,5-dibromo-thiophene-3,4-dicarboxylic acid and 5-aminothiophene-2-carboxamide to dimethyl sulfoxide and mix to form a base solution;
[0013] a2. Add 98% concentrated sulfuric acid to deionized water to form an immersion reaction solution with a mass concentration of 2-6%, and immerse the foam copper substrate in the immersion reaction solution; under an argon atmosphere, add a certain amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride to the base liquid to form a mixed solution, and then add a certain amount of the mixed solution to the immersion reaction solution, heat to 80-120° C. under a continuous argon atmosphere, react for 18-22 hours, cool to room temperature, wash with ethanol, and dry at room temperature for 8-12 hours to obtain a foam copper with a surface loaded with linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)], which is recorded as intermediate A.
[0014] Preferably, in step a1, the amount of 2,5-dibromo-thiophene-3,4-dicarboxylic acid added to each liter of the base liquid is 150-190 g, and the amount of 5-aminothiophene-2-carboxamide added is 130-170 g.
[0015] Preferably, in step a2: the weight of the foam copper substrate immersed in each liter of the immersion reaction liquid is 180-240g; the amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride added per liter of the base liquid is 5-15g; and the volume ratio of the mixed liquid to the immersion reaction liquid is 5-7:2-3.
[0016] Preferably, the step [2] specifically includes the following operations:
[0017] In an argon atmosphere, 4,5-difluorobenzene-1,2-diamine, triphenylphosphine rhodium chloride, and sodium tetraphenylborate are added to ethanol and mixed to form a conversion solution A. The intermediate A is immersed in the conversion solution A, heated to 50-75° C. in a continuous argon atmosphere, reacted for 20-28 hours, cooled to room temperature, washed with deionized water, and dried at room temperature for 6-10 hours to obtain a foam copper with a surface loaded with cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], which is recorded as intermediate B.
[0018] Preferably, the amount of 4,5-difluorobenzene-1,2-diamine added to each liter of the conversion solution A is 170-200 g, the amount of triphenylphosphine rhodium chloride added is 5-10 g, and the amount of sodium tetraphenylborate added is 20-40 g; the weight of the intermediate A immersed in each liter of the conversion solution A is 130-190 g.
[0019] Preferably, the step [3] specifically includes the following operations:
[0020] c1. Add bismuth trioxide, molybdenum trioxide, nitric acid with a mass fraction of 68% and disodium dihydrogen pyrophosphate into deionized water, mix to form a reaction solution, immerse the intermediate B in the reaction solution, heat to 50-70° C. in a water bath, react for 5 to 7 hours, and assemble the Bi2O9Mo2 precursor on the surface of the cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the copper foam, take out the composite copper foam product and dry it for 6 to 8 hours, which is recorded as intermediate C;
[0021] c2. Add neodymium nitrate and ammonium molybdate to deionized water, mix to form a conversion solution B, immerse the intermediate C in the conversion solution B, heat to 150-180°C, react for 3-5 hours, cool to room temperature and dry the product for 6-8 hours to convert the Bi2O9Mo2 precursor into BiNdO9Mo2 nanocrystals, and finally obtain the composite photocatalytic material.
[0022] Preferably, in step c1, the concentration of nitric acid in the reaction solution is 0.5-1 mol / L, the amount of bismuth trioxide added per liter of the reaction solution is 80-100 g, the amount of molybdenum trioxide added is 140-180 g, and the amount of disodium dihydrogen pyrophosphate added is 15-40 g; the amount of intermediate B immersed in each liter of the reaction solution is 180-200 g.
[0023] Preferably, in step c2, the amount of neodymium nitrate added to each liter of the conversion solution B is 60-110 g, and the amount of ammonium molybdate added is 160-190 g; the weight of the intermediate C immersed in each liter of the conversion solution B is 120-160 g.
[0024] The positive effects of the present invention are as follows: the composite photocatalytic degradation material prepared by the method of the present invention is synthesized on the surface of the foam copper by cross-linking poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] organic matter and assembled BiNdO9Mo2 nanocrystals, wherein the cross-linking poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] is formed into a chain structure by thiophene monomers through conjugated bonds, and thus has good conductive properties, a small bandgap, high electron migration, and the amide groups on the long chain make it have good visible light absorption properties; BiNdO9 Mo2 nanocrystals have an orthorhombic crystal structure and belong to the space group Pnma (62). BiNdO9Mo2 nanocrystals have visible light and ultraviolet light photocatalytic activity. In the photocatalytic degradation of sulfamethoxazole by the prepared composite photocatalytic material, the poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] / BiNdO9Mo2 crystals loaded on the surface of the foamed copper facilitate the separation of photogenerated electrons and holes, thereby facilitating the generation of a large number of superoxide radicals and hydroxyl radicals, which can attack the active sites of sulfamethoxazole and cause its rapid degradation.
[0025] In conclusion, the photocatalytic degradation material prepared according to the present invention has photocatalytic degradation properties such as a wide absorption spectrum, high photocatalytic activity and high stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the preparation process of the composite photocatalytic material of the present invention;
[0027] Figure 2 is a schematic structural diagram of the composite photocatalytic material of the present invention;
[0028] Figure 3 The photocatalytic degradation rate of sulfamethoxazole in the simulated sulfamethoxazole-containing wastewater treated by Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0029] Figure 4a , 4b 4 and 4c are relationship diagrams between the number of times of repeated use of Example 1, Comparative Example 1 and Comparative Example 2 to treat simulated sulfamethoxazole-containing wastewater and the photocatalytic degradation rate of sulfamethoxazole. DETAILED DESCRIPTION
[0030] Reference Figure 1 The present invention provides a method for preparing a composite photocatalytic material for degrading sulfamethoxazole, comprising the following steps:
[0031] Step [1] loading linear poly [(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the copper foam substrate, specifically comprising the following operations:
[0032] a1. Add 2,5-dibromo-thiophene-3,4-dicarboxylic acid and 5-aminothiophene-2-carboxamide to dimethyl sulfoxide and mix to form a base solution, wherein the amount of 2,5-dibromo-thiophene-3,4-dicarboxylic acid added per liter of the base solution is 150-190 g, and the amount of 5-aminothiophene-2-carboxamide added is 130-170 g;
[0033] a2. Add 98% concentrated sulfuric acid to deionized water to form a soaking reaction solution with a mass concentration of 2-6%, immerse the foam copper substrate in the soaking reaction solution (the weight of the foam copper substrate immersed in each liter of the soaking reaction solution is 180-240g); under an argon atmosphere, add a certain amount of 1,3-bis(diphenylphosphine)propanepalladium chloride to the base solution (the amount of 1,3-bis(diphenylphosphine)propanepalladium chloride added per liter of the base solution is 5-15g), mix to form a mixed solution, and then add a certain amount of the mixed solution to the soaking The reaction solution (the volume ratio of the mixed solution to the immersion reaction solution is 5-7:2-3) is heated to 80-120° C. in a continuous argon atmosphere, reacted for 18-22 hours, cooled to room temperature, washed with ethanol, and dried at room temperature for 8-12 hours to obtain a foam copper with a linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] loaded on the surface, which is recorded as intermediate A; wherein the structural formula of the linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] is:
[0034]
[0035] Step [2] converting the linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] into a cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], the specific operation is as follows:
[0036] In an argon atmosphere, 4,5-difluorobenzene-1,2-diamine, triphenylphosphine rhodium chloride, and sodium tetraphenylborate were added to ethanol and mixed to form a conversion solution A (the amount of 4,5-difluorobenzene-1,2-diamine added per liter of the conversion solution A was 170 -200g, 5-10g of triphenylphosphine rhodium chloride, and 20-40g of sodium tetraphenylborate), immersing the intermediate A in the conversion solution A (the weight of the intermediate A immersed in the conversion solution A is 130-190g), heating to 50-75°C under a continuous argon atmosphere, reacting for 20-28 hours, cooling to room temperature, washing with deionized water, and drying at room temperature for 6-10 hours to obtain a foam copper with a surface loaded with cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], which is recorded as intermediate B; wherein the structural formula of the cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] is:
[0037]
[0038] Step [3] assembling Bi2GdO3SeI nanocrystals on the surface of the cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] specifically comprises the following operations:
[0039] c1. Add bismuth trioxide, molybdenum trioxide, nitric acid with a mass fraction of 68% and disodium dihydrogen pyrophosphate into deionized water, mix to form a reaction solution (the concentration of nitric acid in the reaction solution is 0.5-1 mol / L, the amount of bismuth trioxide added per liter of the reaction solution is 80-100 g, the amount of molybdenum trioxide added is 140-180 g, and the amount of disodium dihydrogen pyrophosphate added is 15-40 g), immerse the intermediate B in the reaction solution (the amount of intermediate B immersed in each liter of the reaction solution is 180-200 g), heat to 50-70° C. in a water bath, react for 5 to 7 hours, assemble Bi2O9Mo2 precursor on the surface of the cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the foam copper, take out the composite foam copper product and dry it for 6 to 8 hours, which is recorded as intermediate C;
[0040] c2. Add neodymium nitrate and ammonium molybdate to deionized water, mix to form conversion solution B (the amount of neodymium nitrate added to each liter of conversion solution B is 60-110g, and the amount of ammonium molybdate added is 160-190g), immerse the intermediate C in the conversion solution B (the weight of the intermediate C immersed in each liter of the conversion solution B is 120-160g), heat to 150-180°C, react for 3-5 hours, cool to room temperature, and dry the product for 6 to 8 hours to convert the Bi2O9Mo2 precursor into BiNdO9Mo2 nanocrystals, and finally obtain the composite photocatalytic material, the microstructure schematic diagram of which is shown in Figure 2 shown.
[0041] The preferred embodiments of the present invention are described below by way of example.
[0042] Example 1
[0043] Preferred embodiment 1 of the present invention provides a method for preparing a composite photocatalytic material for degrading sulfamethoxazole, comprising the following steps:
[0044] Step [1] loading linear poly [(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the copper foam substrate, specifically comprising the following operations:
[0045] a1. Add 2,5-dibromo-thiophene-3,4-dicarboxylic acid and 5-aminothiophene-2-carboxamide to dimethyl sulfoxide and mix to form a base solution, wherein the amount of 2,5-dibromo-thiophene-3,4-dicarboxylic acid added per liter of the base solution is 180 g, and the amount of 5-aminothiophene-2-carboxamide added is 160 g;
[0046] a2. Add 98% concentrated sulfuric acid to deionized water to form an immersion reaction solution with a mass fraction of sulfuric acid of 4%, immerse the foam copper substrate in the immersion reaction solution (the weight of the foam copper substrate immersed in each liter of the immersion reaction solution is 220g); under an argon atmosphere, add a certain amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride to the base liquid (the amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride added to each liter of the base liquid is 8g), mix to form a mixed solution, and then add a certain amount of the mixed solution to the immersion reaction solution (the volume ratio of the mixed solution to the immersion reaction solution is 7:2), heat to 110°C under a continuous argon atmosphere, react for 21 hours, cool to room temperature, wash with ethanol, and dry at room temperature for 10 hours to obtain a foam copper with a surface loaded with linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)], recorded as intermediate A;
[0047] Step [2] converting the linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] into a cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], the specific operation is as follows:
[0048] In an argon atmosphere, 4,5-difluorobenzene-1,2-diamine, triphenylphosphine rhodium chloride, and sodium tetraphenylborate were added to ethanol and mixed to form a conversion solution A (the amount of 4,5-difluorobenzene-1,2-diamine added per liter of the conversion solution A was 190 g, the amount of triphenylphosphine rhodium chloride added was 8 g, and the amount of sodium tetraphenylborate added was 30 g), the intermediate A was immersed in the conversion solution A (the weight of the intermediate A immersed in the conversion solution A was 180 g), heated to 70° C. under a continuous argon atmosphere, reacted for 22 hours, cooled to room temperature, washed with deionized water, and dried at room temperature for 8 hours to obtain a foam copper with a surface loaded with cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], recorded as intermediate B;
[0049] Step [3] assembling Bi2GdO3SeI nanocrystals on the surface of the cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] specifically comprises the following operations:
[0050] c1. Add bismuth trioxide, molybdenum trioxide, nitric acid with a mass fraction of 68% and disodium dihydrogen pyrophosphate into deionized water, mix to form a reaction solution (the concentration of nitric acid in the reaction solution is 0.8 mol / L, the amount of bismuth trioxide added per liter of the reaction solution is 90 g, the amount of molybdenum trioxide added is 170 g, and the amount of disodium dihydrogen pyrophosphate added is 30 g), immerse the intermediate B in the reaction solution (the amount of intermediate B immersed in each liter of the reaction solution is 190 g), heat to 60° C. in a water bath, react for 6 hours, and assemble Bi2O9Mo2 precursor on the surface of the cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the foam copper, take out the composite foam copper product and dry it for 7 hours, which is recorded as intermediate C;
[0051] c2. Add neodymium nitrate and ammonium molybdate to deionized water, mix to form conversion solution B (the amount of neodymium nitrate added to each liter of conversion solution B is 100 g, and the amount of ammonium molybdate added is 190 g), immerse the intermediate C in the conversion solution B (the weight of the intermediate C immersed in each liter of the conversion solution B is 150 g), heat to 170°C, react for 4 hours, cool to room temperature, and dry the product for 7 hours to convert the Bi2O9Mo2 precursor into BiNdO9Mo2 nanocrystals, and finally obtain the composite photocatalytic material (foam copper loaded with poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] / BiNdO9Mo2 nanocrystals), which is recorded as Example 1.
[0052] Comparative Example 1
[0053] This comparative example 1 provides a method for preparing a composite photocatalytic material for degrading sulfamethoxazole, comprising the following steps:
[0054] Step [1] loading linear poly [(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the copper foam substrate, specifically comprising the following operations:
[0055] a1. Add 2,5-dibromo-thiophene-3,4-dicarboxylic acid and 5-aminothiophene-2-carboxamide to dimethyl sulfoxide and mix to form a base solution, wherein per liter of the base solution, 2,5-dibromo-thiophene-3,4-dicarboxylic acid is added in an amount of 160 g and 5-aminothiophene-2-carboxamide is added in an amount of 140 g;
[0056] a2. Add 98% concentrated sulfuric acid to deionized water to form a soaking reaction solution with a mass concentration of 4%, immerse the foam copper substrate in the soaking reaction solution (the weight of the foam copper substrate immersed in each liter of the soaking reaction solution is 220g); under an argon atmosphere, add a certain amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride to the base liquid (the amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride added to the base liquid is 7g), mix to form a mixed solution, and then add a certain amount of the mixed solution to the soaking reaction solution (the volume ratio of the mixed solution to the soaking reaction solution is 5:2), heat to 90°C under a continuous argon atmosphere, react for 20 hours, cool to room temperature, wash with ethanol, and dry at room temperature for 10 hours to obtain a foam copper with a surface loaded with linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)], recorded as intermediate A;
[0057] Step [2] assembling Bi2GdO3SeI nanocrystals on the surface of the linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] specifically comprises the following operations:
[0058] c1. Add bismuth trioxide, molybdenum trioxide, nitric acid with a mass fraction of 68% and disodium dihydrogen pyrophosphate into deionized water, mix to form a reaction solution (the concentration of nitric acid in the reaction solution is 0.75 mol / L, the amount of bismuth trioxide added to each liter of the reaction solution is 90 g, the amount of molybdenum trioxide added is 170 g, and the amount of disodium dihydrogen pyrophosphate added is 30 g), immerse the intermediate A in the reaction solution (the amount of intermediate A immersed in each liter of the reaction solution is 190 g), heat to 60° C. in a water bath, react for 6 hours, and assemble the Bi2O9Mo2 precursor on the surface of the linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the copper foam, take out the composite copper foam product and dry it for 7 hours, which is recorded as intermediate C;
[0059] c2. Add neodymium nitrate and ammonium molybdate to deionized water, mix to form conversion solution B (the amount of neodymium nitrate added to each liter of conversion solution B is 80 g, and the amount of ammonium molybdate added is 170 g), immerse the intermediate C in the conversion solution B (the weight of the intermediate C immersed in each liter of the conversion solution B is 140 g), heat to 160°C, react for 4 hours, cool to room temperature, and dry the product for 7 hours to convert the Bi2O9Mo2 precursor into BiNdO9Mo2 nanocrystals, and finally obtain the composite photocatalytic material (foam copper loaded linear poly [(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] / BiNdO9Mo2 nanocrystals), which is recorded as Comparative Example 1.
[0060] Comparative Example 2
[0061] This comparative example 2 provides a method for preparing a composite photocatalytic material for degrading sulfamethoxazole, comprising the following steps:
[0062] Step [1] loading linear poly [(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the copper foam substrate, specifically comprising the following operations:
[0063] a1. Add 2,5-dibromo-thiophene-3,4-dicarboxylic acid and 5-aminothiophene-2-carboxamide to dimethyl sulfoxide and mix to form a base solution, wherein the amount of 2,5-dibromo-thiophene-3,4-dicarboxylic acid added per liter of the base solution is 180 g, and the amount of 5-aminothiophene-2-carboxamide added is 160 g;
[0064] a2. Add 98% concentrated sulfuric acid to deionized water to form an immersion reaction solution with a mass concentration of 5%, immerse the foam copper substrate in the immersion reaction solution (the weight of the foam copper substrate immersed in each liter of the immersion reaction solution is 200g); under an argon atmosphere, add a certain amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride to the base liquid (the amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride added to each liter of the base liquid is 10g), mix to form a mixed solution, and then add a certain amount of the mixed solution to the immersion reaction solution (the volume ratio of the mixed solution to the immersion reaction solution is 7:3), heat to 100°C under a continuous argon atmosphere, react for 21 hours, cool to room temperature, wash with ethanol, and dry at room temperature for 10 hours to obtain a foam copper with a linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] loaded on the surface, recorded as intermediate A;
[0065] Step [2] converting the linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] into a cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], the specific operation is as follows:
[0066] In an argon atmosphere, 4,5-difluorobenzene-1,2-diamine, triphenylphosphine rhodium chloride, and sodium tetraphenylborate were added to ethanol and mixed to form a conversion solution A (the amount of 4,5-difluorobenzene-1,2-diamine added per liter of the conversion solution A was 190 g, the amount of triphenylphosphine rhodium chloride added was 8 g, and the amount of sodium tetraphenylborate added was 30 g), and the intermediate A was immersed in the conversion solution A (the weight of the intermediate A immersed in the conversion solution A was 150 g), heated to 65° C. under a continuous argon atmosphere, reacted for 22 hours, cooled to room temperature, washed with deionized water, and dried at room temperature for 8 hours to obtain a foam copper with a surface loaded with cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], which was recorded as Comparative Example 2.
[0067] In order to analyze the absorption spectrum characteristics, photocatalytic activity and photocatalytic degradation removal rate of sulfamethoxazole in Example 1, Comparative Example 1 and Comparative Example 2 for treating sulfamethoxazole-containing sewage, 0.5g sulfamethoxazole was dissolved in 50mL methanol to form a mother liquor, and the mother liquor was added with deionized water to form a simulated sulfamethoxazole-containing sewage with a concentration of 10mg / L. 100ml of simulated sulfamethoxazole-containing sewage was poured into a beaker, and 10g of Example 1, Comparative Example 1 and Comparative Example 2 were placed in the beaker respectively. A xenon lamp light source was used under the conditions of working current 22A and working voltage 20V, ultraviolet light (λ=360nm) and visible light (λ=550nm) were used to irradiate Comparative Example 1, Comparative Example 2 and Example 1 for one hour, and high performance liquid chromatography (HPLC) was used to analyze the residual concentration of sulfamethoxazole, and then the photocatalytic degradation rate of sulfamethoxazole in the sulfamethoxazole-containing sewage was calculated. The results are as follows: Figure 3 As shown in the figure, the photocatalytic degradation rates of sulfamethoxazole under ultraviolet light and visible light in Example 1 are 99% and 91% respectively, the photocatalytic degradation rates of sulfamethoxazole under ultraviolet light and visible light in Comparative Example 1 are 87% and 76% respectively, and the photocatalytic degradation rates of sulfamethoxazole under ultraviolet light and visible light in Comparative Example 2 can only reach 42% and 34% respectively. Under the above-mentioned treatment conditions and treatment time, Example 1, Comparative Example 1 and Comparative Example 2 are repeatedly used, and the relationship between the number of uses and the photocatalytic degradation rate of sulfamethoxazole is as shown respectively. Figure 4a -c, it can be seen from the figure that the photocatalytic degradation rate of sulfamethoxazole in the fifth treatment of simulated sulfamethoxazole-containing wastewater under ultraviolet light and visible light conditions in Example 1 can still reach 94% and 88%; however, the photocatalytic degradation rate of sulfamethoxazole in the fifth treatment of simulated sulfamethoxazole-containing wastewater in Comparative Example 1 and Comparative Example 2 is significantly reduced.
[0068] In summary, the photocatalytic degradation material prepared according to the present invention has the performance of photocatalytic degradation of sulfamethoxazole with a wide absorption spectrum, high photocatalytic activity and high stability.
[0069] To illustrate in further detail, three additional examples are provided below.
[0070] Example 2
[0071] Preferred embodiment 2 of the present invention provides a method for preparing a composite photocatalytic material for degrading sulfamethoxazole, comprising the following steps:
[0072] Step [1] loading linear poly [(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the copper foam substrate, specifically comprising the following operations:
[0073] a1. Add 2,5-dibromo-thiophene-3,4-dicarboxylic acid and 5-aminothiophene-2-carboxamide to dimethyl sulfoxide and mix to form a base solution, wherein per liter of the base solution, 2,5-dibromo-thiophene-3,4-dicarboxylic acid is added in an amount of 150 g and 5-aminothiophene-2-carboxamide is added in an amount of 130 g;
[0074] a2. Add 98% concentrated sulfuric acid to deionized water to form an immersion reaction solution with a mass concentration of 2%, immerse the foam copper substrate in the immersion reaction solution (the weight of the foam copper substrate immersed in each liter of the immersion reaction solution is 180g); under an argon atmosphere, add a certain amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride to the base liquid (the amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride added to the base liquid is 5g), mix to form a mixed solution, and then add a certain amount of the mixed solution to the immersion reaction solution (the volume ratio of the mixed solution to the immersion reaction solution is 5:3), heat to 120°C under a continuous argon atmosphere, react for 18 hours, cool to room temperature, wash with ethanol, and dry at room temperature for 12 hours to obtain a foam copper with a linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] loaded on the surface, recorded as intermediate A;
[0075] Step [2] converting the linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] into a cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], the specific operation is as follows:
[0076] In an argon atmosphere, 4,5-difluorobenzene-1,2-diamine, triphenylphosphine rhodium chloride, and sodium tetraphenylborate were added to ethanol and mixed to form a conversion solution A (the amount of 4,5-difluorobenzene-1,2-diamine added per liter of the conversion solution A was 170 g, the amount of triphenylphosphine rhodium chloride added was 5 g, and the amount of sodium tetraphenylborate added was 40 g), the intermediate A was immersed in the conversion solution A (the weight of the intermediate A immersed in the conversion solution A was 190 g), heated to 75° C. under a continuous argon atmosphere, reacted for 20 hours, cooled to room temperature, washed with deionized water, and dried at room temperature for 10 hours to obtain a foam copper with a surface loaded with cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], recorded as intermediate B;
[0077] Step [3] assembling Bi2GdO3SeI nanocrystals on the surface of the cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] specifically comprises the following operations:
[0078] c1. Add bismuth trioxide, molybdenum trioxide, nitric acid with a mass fraction of 68% and disodium dihydrogen pyrophosphate into deionized water, mix to form a reaction solution (the concentration of nitric acid in the reaction solution is 1 mol / L, the amount of bismuth trioxide added to each liter of the reaction solution is 100 g, the amount of molybdenum trioxide added is 140 g, and the amount of disodium dihydrogen pyrophosphate added is 15 g), immerse the intermediate B in the reaction solution (the amount of intermediate B immersed in each liter of the reaction solution is 180 g), heat to 70° C. in a water bath, react for 5 hours, and assemble the Bi2O9Mo2 precursor on the surface of the cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the foam copper, take out the composite foam copper product and dry it for 8 hours, which is recorded as intermediate C;
[0079] c2. Add neodymium nitrate and ammonium molybdate to deionized water, mix to form conversion solution B (the amount of neodymium nitrate added to each liter of conversion solution B is 110 g, and the amount of ammonium molybdate added is 160 g), immerse the intermediate C in the conversion solution B (the weight of the intermediate C immersed in each liter of the conversion solution B is 120 g), heat to 150°C, react for 5 hours, cool to room temperature, and dry the product for 8 hours to convert the Bi2O9Mo2 precursor into BiNdO9Mo2 nanocrystals, and finally obtain the composite photocatalytic material.
[0080] Example 3
[0081] Preferred embodiment 3 of the present invention provides a method for preparing a composite photocatalytic material for degrading sulfamethoxazole, comprising the following steps:
[0082] Step [1] loading linear poly [(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the copper foam substrate, specifically comprising the following operations:
[0083] a1. Add 2,5-dibromo-thiophene-3,4-dicarboxylic acid and 5-aminothiophene-2-carboxamide to dimethyl sulfoxide and mix to form a base solution, wherein per liter of the base solution, 2,5-dibromo-thiophene-3,4-dicarboxylic acid is added in an amount of 190 g and 5-aminothiophene-2-carboxamide is added in an amount of 170 g;
[0084] a2. Add 98% concentrated sulfuric acid to deionized water to form an immersion reaction solution with a mass concentration of 6%, immerse the foam copper substrate in the immersion reaction solution (the weight of the foam copper substrate immersed in each liter of the immersion reaction solution is 240g); under an argon atmosphere, add a certain amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride to the base liquid (the amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride added to the base liquid is 15g), mix to form a mixed solution, and then add a certain amount of the mixed solution to the immersion reaction solution (the volume ratio of the mixed solution to the immersion reaction solution is 7:2), heat to 80°C under a continuous argon atmosphere, react for 22 hours, cool to room temperature, wash with ethanol, and dry at room temperature for 8 hours to obtain a foam copper with a linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] loaded on the surface, recorded as intermediate A;
[0085] Step [2] converting the linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] into a cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], the specific operation is as follows:
[0086] In an argon atmosphere, 4,5-difluorobenzene-1,2-diamine, triphenylphosphine rhodium chloride, and sodium tetraphenylborate are added to ethanol and mixed to form a conversion solution A (the amount of 4,5-difluorobenzene-1,2-diamine added per liter of the conversion solution A is 200 g, the amount of triphenylphosphine rhodium chloride added is 10 g, and the amount of sodium tetraphenylborate added is 20 g), the intermediate A is immersed in the conversion solution A (the weight of the intermediate A immersed in the conversion solution A is 130 g), heated to 50° C. under a continuous argon atmosphere, reacted for 28 hours, cooled to room temperature, washed with deionized water, and dried at room temperature for 6 hours to obtain a foam copper with a surface loaded with cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], recorded as intermediate B;
[0087] Step [3] assembling Bi2GdO3SeI nanocrystals on the surface of the cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] specifically comprises the following operations:
[0088] c1. Add bismuth trioxide, molybdenum trioxide, nitric acid with a mass fraction of 68% and disodium dihydrogen pyrophosphate into deionized water, mix to form a reaction solution (the concentration of nitric acid in the reaction solution is 0.5 mol / L, the amount of bismuth trioxide added per liter of the reaction solution is 80 g, the amount of molybdenum trioxide added is 180 g, and the amount of disodium dihydrogen pyrophosphate added is 40 g), immerse the intermediate B in the reaction solution (the amount of intermediate B immersed in each liter of the reaction solution is 200 g), heat to 50° C. in a water bath, react for 7 hours, and assemble Bi2O9Mo2 precursor on the surface of the cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the foam copper, take out the composite foam copper product and dry it for 6 hours, which is recorded as intermediate C;
[0089] c2. Add neodymium nitrate and ammonium molybdate to deionized water, mix to form conversion solution B (the amount of neodymium nitrate added to each liter of conversion solution B is 60 g, and the amount of ammonium molybdate added is 190 g), immerse the intermediate C in the conversion solution B (the weight of the intermediate C immersed in each liter of the conversion solution B is 160 g), heat to 180°C, react for 3 hours, cool to room temperature, and dry the product for 6 hours to convert the Bi2O9Mo2 precursor into BiNdO9Mo2 nanocrystals, and finally obtain the composite photocatalytic material.
[0090] Example 4
[0091] Preferred embodiment 4 of the present invention provides a method for preparing a composite photocatalytic material for degrading sulfamethoxazole, comprising the following steps:
[0092] Step [1] loading linear poly [(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the copper foam substrate, specifically comprising the following operations:
[0093] a1. Add 2,5-dibromo-thiophene-3,4-dicarboxylic acid and 5-aminothiophene-2-carboxamide to dimethyl sulfoxide and mix to form a base solution, wherein per liter of the base solution, 2,5-dibromo-thiophene-3,4-dicarboxylic acid is added in an amount of 170 g and 5-aminothiophene-2-carboxamide is added in an amount of 150 g;
[0094] a2. Add 98% concentrated sulfuric acid to deionized water to form an immersion reaction solution with a mass concentration of 4%, immerse the foam copper substrate in the immersion reaction solution (the weight of the foam copper substrate immersed in each liter of the immersion reaction solution is 210g); under an argon atmosphere, add a certain amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride to the base liquid (the amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride added to each liter of the base liquid is 10g), mix to form a mixed solution, and then add a certain amount of the mixed solution to the immersion reaction solution (the volume ratio of the mixed solution to the immersion reaction solution is 5:3), heat to 100°C under a continuous argon atmosphere, react for 20 hours, cool to room temperature, wash with ethanol, and dry at room temperature for 10 hours to obtain a foam copper with a linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] loaded on the surface, recorded as intermediate A;
[0095] Step [2] converting the linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] into a cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], the specific operation is as follows:
[0096] In an argon atmosphere, 4,5-difluorobenzene-1,2-diamine, triphenylphosphine rhodium chloride, and sodium tetraphenylborate were added to ethanol and mixed to form a conversion solution A (the amount of 4,5-difluorobenzene-1,2-diamine added per liter of the conversion solution A was 185 g, the amount of triphenylphosphine rhodium chloride added was 8 g, and the amount of sodium tetraphenylborate added was 30 g), the intermediate A was immersed in the conversion solution A (the weight of the intermediate A immersed in the conversion solution A was 160 g), heated to 65° C. under a continuous argon atmosphere, reacted for 24 hours, cooled to room temperature, washed with deionized water, and dried at room temperature for 8 hours to obtain a foam copper with a surface loaded with cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], recorded as intermediate B;
[0097] Step [3] assembling Bi2GdO3SeI nanocrystals on the surface of the cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] specifically comprises the following operations:
[0098] c1. Add bismuth trioxide, molybdenum trioxide, nitric acid with a mass fraction of 68% and disodium dihydrogen pyrophosphate into deionized water, mix to form a reaction solution (the concentration of nitric acid in the reaction solution is 0.8 mol / L, the amount of bismuth trioxide added per liter of the reaction solution is 90 g, the amount of molybdenum trioxide added is 160 g, and the amount of disodium dihydrogen pyrophosphate added is 29 g), immerse the intermediate B in the reaction solution (the amount of intermediate B immersed in each liter of the reaction solution is 190 g), heat to 60° C. in a water bath, react for 6 hours, and assemble Bi2O9Mo2 precursor on the surface of the cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the foam copper, take out the composite foam copper product and dry it for 7 hours, which is recorded as intermediate C;
[0099] c2. Add neodymium nitrate and ammonium molybdate to deionized water, mix to form conversion solution B (the amount of neodymium nitrate added to each liter of conversion solution B is 85 g, and the amount of ammonium molybdate added is 175 g), immerse the intermediate C in the conversion solution B (the weight of the intermediate C immersed in each liter of the conversion solution B is 140 g), heat to 165°C, react for 4 hours, cool to room temperature, and dry the product for 7 hours to convert the Bi2O9Mo2 precursor into BiNdO9Mo2 nanocrystals, and finally obtain the composite photocatalytic material.
[0100] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a composite photocatalytic material for degrading sulfamethoxazole, characterized in that: The following steps are included: Step [1] Loading linear poly [(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of a foam copper substrate; Step [2] converting the linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)] into a cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)]; Step [3] assembles Bi2GdO3SeI nanocrystals on the surface of the cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] 2. The method for preparing a composite photocatalytic material for degrading sulfamethoxazole according to claim 1, characterized in that: The step [1] specifically includes the following operations: a1. Add 2,5-dibromo-thiophene-3,4-dicarboxylic acid and 5-aminothiophene-2-carboxamide to dimethyl sulfoxide and mix to form a base solution; a2. Add 98% concentrated sulfuric acid to deionized water to form an immersion reaction solution with a mass concentration of 2-6%, and immerse the foam copper substrate in the immersion reaction solution; under an argon atmosphere, add a certain amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride to the base liquid to form a mixed solution, and then add a certain amount of the mixed solution to the immersion reaction solution, heat to 80-120° C. under a continuous argon atmosphere, react for 18-22 hours, cool to room temperature, wash with ethanol, and dry at room temperature for 8-12 hours to obtain a foam copper with a surface loaded with linear poly[(2,5-dibromo-4-carbonylthiophene)-(2,5-diamidothiophene)], which is recorded as intermediate A.
3. The method for preparing a composite photocatalytic material for degrading sulfamethoxazole according to claim 2, characterized in that: In step a1, the amount of 2,5-dibromo-thiophene-3,4-dicarboxylic acid added to each liter of the base liquid is 150-190 g, and the amount of 5-aminothiophene-2-carboxamide added is 130-170 g.
4. The method for preparing a composite photocatalytic material for degrading sulfamethoxazole according to claim 2, characterized in that: In step a2: the weight of the foam copper substrate immersed in the soaking reaction liquid per liter is 180-240g; the amount of 1,3-bis(diphenylphosphinopropanepalladium) chloride added per liter of the base liquid is 5-15g; the volume ratio of the mixed liquid to the soaking reaction liquid is 5-7:2-3.
5. The method for preparing a composite photocatalytic material for degrading sulfamethoxazole according to claim 1, characterized in that: The step [2] specifically includes the following operations: In an argon atmosphere, 4,5-difluorobenzene-1,2-diamine, triphenylphosphine rhodium chloride, and sodium tetraphenylborate are added to ethanol and mixed to form a conversion solution A. The intermediate A is immersed in the conversion solution A, heated to 50-75° C. in a continuous argon atmosphere, reacted for 20-28 hours, cooled to room temperature, washed with deionized water, and dried at room temperature for 6-10 hours to obtain a foam copper with a surface loaded with cross-linked poly [(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)], which is recorded as intermediate B.
6. The method for preparing a composite photocatalytic material for degrading sulfamethoxazole according to claim 5, characterized in that: The amount of 4,5-difluorobenzene-1,2-diamine added to each liter of the conversion solution A is 170-200 g, the amount of triphenylphosphine rhodium chloride added is 5-10 g, and the amount of sodium tetraphenylborate added is 20-40 g; the weight of the intermediate A immersed in each liter of the conversion solution A is 130-190 g.
7. The method for preparing a composite photocatalytic material for degrading sulfamethoxazole according to claim 1, characterized in that: The step [3] specifically includes the following operations: c1. Add bismuth trioxide, molybdenum trioxide, nitric acid with a mass fraction of 68% and disodium dihydrogen pyrophosphate into deionized water, mix to form a reaction solution, immerse the intermediate B in the reaction solution, heat to 50-70° C. in a water bath, react for 5 to 7 hours, and assemble the Bi2O9Mo2 precursor on the surface of the cross-linked poly[(2,5-diaminodifluorophenyl-4-carbonylthiophene)-(2,5-diamidothiophene)] on the surface of the copper foam, take out the composite copper foam product and dry it for 6 to 8 hours, which is recorded as intermediate C; c2. Add neodymium nitrate and ammonium molybdate to deionized water, mix to form a conversion solution B, immerse the intermediate C in the conversion solution B, heat to 150-180°C, react for 3-5 hours, cool to room temperature and dry the product for 6-8 hours to convert the Bi2O9Mo2 precursor into BiNdO9Mo2 nanocrystals, and finally obtain the composite photocatalytic material.
8. The method for preparing a composite photocatalytic material for degrading sulfamethoxazole according to claim 7, characterized in that: In step c1, the concentration of nitric acid in the reaction solution is 0.5-1 mol / L, the amount of bismuth trioxide added per liter of the reaction solution is 80-100 g, the amount of molybdenum trioxide added is 140-180 g, and the amount of disodium dihydrogen pyrophosphate added is 15-40 g; the amount of intermediate B immersed in each liter of the reaction solution is 180-200 g.
9. The method for preparing a composite photocatalytic material for degrading sulfamethoxazole according to claim 7, characterized in that: In step c2, the amount of neodymium nitrate added to each liter of the conversion solution B is 60-110 g, and the amount of ammonium molybdate added is 160-190 g; the weight of the intermediate C immersed in each liter of the conversion solution B is 120-160 g.
Citation Information
Patent Citations
Preparation method of catalytic degradation agent for treating phenolic wastewater by ultrasonic synergistic Fenton
CN118681598A
Preparation method of foamy copper-based organic catalytic material for treating chloride ion wastewater
CN118831648A